Travel health attitudes among Turkish business travellers to African countries. Issue 6 (November 2016) - Selcuk, Engin Burak; Kayabas, Uner; Binbasioglu, Hulisi; Otlu, Baris; Bayindir, Yasar; Bozdogan, Bulent; Karatas, Mehmet
Summary: Background: The number of international travellers is increasing worldwide. Although health risks related to international travel are important and generally well-understood, the perception of these risks was unclear among Turkish travellers. We aimed to evaluate the attitudes and health risk awareness of Turkish travellers travelling to African countries. Method: A survey was performed of Turkish travellers bound for Africa from Istanbul International Ataturk Airport in July 2013. Results: A total of 124 travellers were enrolled in the study. Among them, 62.9% had information about their destination but only 11.3% had looked for information on health problems related to travel and their destination. Of all travellers, 53.2% had at least one vaccination before travelling. The most commonly administered vaccine was for typhoid. Among the travellers, 69.3% and 80.6% had "no idea" about yellow fever vaccination and malaria prophylaxis, respectively. A positive correlation was found between a higher level of travellers' education and receiving the recommended vaccination for the destination. Conclusions: Our study revealed significant gaps in the vaccination and chemoprophylaxis uptake of Turkish travellers departing to Africa. An awareness and training program should be developed for travellers, as well as public health workers, to address health risks related to travel.